2022
DOI: 10.1155/2022/9521900
|View full text |Cite|
|
Sign up to set email alerts
|

The Mechanism of Oxidative Stress in Cells Isolation, Identification, and Genome-Wide Sequence Analysis of Nitrite Amylolytic Bacillus

Abstract: To improve the quality of traditional fermented pickles and reduce the nitrite content in the production process of pickles, the target bacteria for efficient nitrite degradation were screened from traditional fermented pickles. Pickles (picked vegetables), a traditional dish favored by many Chinese, are mildly salted and lactic acid-fermented vegetables in China. However, the presence of nitrite in pickles is a bottleneck which limits further development of the pickle industry. More attention is drawn to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%